Contemporary economics : an applications approach - Carbaugh, Robert J. (Australia : South-Western College Publishing, 2001)
Economics
2003-04-15
Keywords: Economics; Microeconomy; Macroeconomy; Demand; Supply; Production; Monopoly; Labor market; Unemployment; Fiscal policy; International economy; Budget; International finance